Perhitungan Produktivitas Mesin Perfect Binding (Yoshino) dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) pada PT. XYZ - Arif Rahman; Surya Perdana (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
Productivity is an important factor to influence the performance of a company. PT. XYZ is a company engaged in printing business. The object of research is Yoshino inline binding machine in the company. The problems caused by this machine, such as hindered and less than maximum production, downtime, breakdown, and setup and adjustment, result in the decrease in productivity. The purpose of this research is to know the calculation of Overall Equipment Effetiviness (OEE) on Yoshino Machine, to know the difference of calculation result from March to May 2015 period and from March to May 2016 and to know some factors causing the decrease in productivity. This research uses the Overall Equipment Effectiveness (OEE) method. Based on the calculation of Overall Equipment Effetiviness (OEE) on Yoshino Machinery, March-May 2015 period compared to March-May 2016 period, the result in March is of 60.14%, April of 57.92%, and May of 59.92%. In general, OEE achievement increases every month, but not yet reached the World Class OEE criteria. The low value of OEE obtained from the Yoshino Machine is due to four factors: operator’s less knowledge of machine (Human), unstable glue temperature (Engine), late suppliers (Material) and inefficient cutter replacing time (Method).